HUBUNGAN KELINCAHAN DENGAN DRIBBLING SEPAKBOLA PADA TIM SMA 2 RAMBAH HILIR KAB ROHUL - Asri '; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the researcher’s observation on Football Team Of SMAN 2 Rambah Hilir Rokan Hulu District. Researcher found many student have deficiency of dribbling. Students often lose the ball, control of the ball was not good, stiil rigidity of movement in dribbling. The purpose of this research is to see how much the contrubution of the agility with dribbling of football team SMAN 2 Rambah Hilir Rokan Hulu Dsitrict . Population in this research is all students in Football Team of SMAN 2 Rambah amount 25 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 25 people. Research instrument used dogging run test to agility and soccer dribbling test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : that is significant corelation between agility (X) with soccer dribbling (Y) , which shows correlation rhitung = 0,840>rtabel = 0,404.Key word: Agility, Dribbling.